Thailand : Financial Sector Assessment Program; Detailed Assessment on the Implementation of the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents key findings of the detailed assessment on the implementation of the International Organization of Securities Commissions (IOSCO) objectives and principles of securities regulation for Thailand. The assessment recommends creating a formal coordination mechanism among governmental agencies with regulatory authority over capital markets. The Securities and Exchange Commission (SEC) should amend its code of conduct and provide that restrictions on securities investments by its staff also applies to spouses, minor children, and all other accounts over which an employee has the authority to make investment decisions.